Evaluability assessment for Impact Evaluation: Guidance, checklists an d decision support - Peersman, Greet; Guijt, Irene; Pasanen, Tiina (ODI, 2015)
This guidance note focuses on the utility of, and guidance for, evalua bility assessment before undertaking an impact evaluation. The primary audience for this guidance note is evaluators conducting an evaluabil ity assessment for impact evaluation. The secondary audience is people commissioning or managing an evaluability assessment for impact evalu ation, as well as funders of an impact evaluation. Sections one and tw o provide an overview of evaluability assessment and how it can be use d for impact evaluation. Section three provides guidance for planning to undertake an evaluability assessment for impact evaluation. This is informative for all intended users of the guidance note. Section four includes checklists and decision support for evaluability assessments . The checklist is geared to those conducting the evaluability assessm ent and can be adapted to suit a particular context or purpose. The de cision support provides those conducting an evaluability assessment wi th evidence-based recommendations for impact evaluation funders and co mmissioners, about whether, when and how to proceed with the evaluatio n. Sections five and six provide guidance on what to do after the asse ssment is concluded, and offer lessons learned from evaluability asses sments in practice.